Didáctica lúcida para el desarrollo de las habilidades comunicativas “hablar y escuchar” en los estudiantes del 5to grado de primaria de la I.E Matilde Del Águila - Valdivia Guevara, Carmen (2014)
The present investigation called playful Teaching for development of communication skills i•talk and listen" in the 5th grade students of Primary Education School "Eagle Matilde Velásquez" No. 00537- Rioja, 2014" From the perspective of understanding that teaching is playful learning system containing interactive science teaching that develop communication skills components. These allow develop effective interrelation of communication processes in society. As previously mentioned, communication skills are gradual processes aimed at effective development of any communicative act, administered by a suitable application of playful teaching. Within a playful educational and pedagogical approach to teaching that has as one of its priorities contribute to the development of teaching regional and local learning. Therefore, from the local, from this research is that the question which we assume was posed as follows: To what extent playful didactic develop communication skills "speaking and listening" to the students of the 5th grade of primary school the "Matilde Velásquez Eagle", No. 00537, Rioja 2014? In the present investigation the following problem: This playful didactic research to improve communication skills "talk and listen" in the 5th grade students of primary school level "Eagle Matilde Velásquez" No. 00537, Rioja 2014? lt arises because students 5th primary level educational institution Matilde Eagle Velasquez No. 00537, have difficulties during the process of learning because students lack of communication (speaking and listening) skills because no employs adequate didactic interest for instant communication process. lt aims to salve the problem intervening through the application of playful teaching to improve the effectiveness of communication process and thus optimize the development of communication skills "talk and listen" by pursuing Apply playful teaching in developing skills communicative "talk and listen" in the 5th grade students of primary school level "Eagle Matilde Velásquez" No. 00537, Rioja. Applying the hypothesis whose playfull Didactics, then significantly developed communication skills "talk and listen" in the 5th grade students of primary school level "Eagle Matilde Velásquez" No. 00537, Rioja. In analyzing the results of the investigation found that the application of playful educational development of communication skills "talk and listen" in the 5th grade students of Primary Education School "Eagle Matilde Velásquez was significant because achieving development of communication skills of speaking and listening is prominent ie in the process of learning for most students were able to have the ability to make the communication process well. Finally the scope of the investigation constitute a contribution to the local, regional and national education.